PERAN KELUARGA DALAM PEMENUHAN KEBUTUHAN SPIRITUALITAS PADA PASIEN YANG DIRAWAT DI RUANG ICU RSUD SAYANG RAKYAT - Syahrir; Fatmawati (Jurnal Ilmiah Keperawatan dan Kebidanan Holistic Care, 2019)
Spirituality is something that is believed by someone in relation to a higher power (God), which creates a need for and love for the existence of God, and apologizes for all mistakes that have been made. Spirituality is the only support and source of individual strength in dealing with illness. The purpose of this study was to determine the role of the family in fulfilling spiritual needs in patients treated in the ICU room at Sayang Rakyat Regional General Hospital. The design in this study is research using a survey approach. The research was conducted in the ICU Room of the Sayang Rakyat Hospital, Prov. South Sulawesi with a total sample of 32 respondents. The results showed that 29 respondents obtained good family role values and 3 respondents who had poor family roles. The conclusion in this study is that most families have a good role in fulfilling the spiritual needs of patients treated in the ICU room of the Sayang Rakyat Regional General Hospital. The advice from this study is that it is best if the provision of care to patients does not only focus on meeting the patient's physical and psychological needs, but also refers to the patient's spiritual needs which coexist with their physical needs